CO2-responsive aqueous foams stabilized by pseudogemini surfactants - Wang, Zengzi; Ren, Gaihuan; Yang, Jiawen; Xu, Zhenghe; Sun, Dejun (Journal of colloid and interface science, 2019)
[Display omitted] To obtain surfactants with superior surface activity and responsive behavior, “pseudogemini” surfactants (short for D-LCFA) are synthesized by mixing long chain fatty acids (LCFA) and polyetheramine D 230 at fixed molar ratio (2:1). Non-covalently bonded building blocks indicate that CO2-responsive aqueous foams can be obtained by utilizing such pseudogemini surfactants. 1H NMR and FT-IR characterizations prove that the building blocks of these surfactants are associated by electrostatic interaction. The synthesis (Brønsted acid-base reaction) is simple and eco-friendly. “Pseudogemini” structure enables D-LCFA to reduce surface tension of aqueous solution effectively, thus facilitating foam generation. Rheograms, FF-TEM and Cryo-TEM results prove that different aggregates in D-LCFA aqueous solutions lead to different foam properties. Bubbling of CO2 for about 30 s leads to the rupture of aqueous foams generated by D-LCFA, while removing CO2 by bubbling of N2 at 65 °C for 10 min enables re-generation of foams. The CO2-responsive foaming properties can be attributed to dissociation of D-LCFA upon bubbling of CO2 and re-association upon removal of CO2. The effective CO2-responsive foams can be applied to many areas, such as foam fracturing, foam enhanced oil recovery or recovering of radioactive materials.